Mechanistic Study on Microbial Degradation and Transformation of Hexachloro-1,3-butadiene under Anoxic Conditions - Qian, Xinyue; Wang, Xin; Fu, Guoqiang; Liu, Xinyi; Wang, Enxu (International Journal of Social Sciences and Public Administration, 2024)
Hexachlorotrietadiene (HCBD) is a volatile organohalogen commonly found in the environments due to its past applications in products such as transformers, hydraulic oil and heat transfer liquid. Despite regulations prohibiting its intentional production by some countries (e.g., the U.S., Canada, several Europe countries), HCBD continues to be produced and released unintentionally through manufacturing processes of other chlorinated compounds and improper waste disposal. In the year 2015 and 2017, it was listed under Annex A and C of the Stockholm Convention on Persistent Organic Pollutants, respectively. Recently, this pollutant was strictly regulated by the Chinese government in 2023. Studies focusing on the HCBD degradation under oxic conditions or co-metabolic transformation have been reported; nevertheless, research on the environmental fate and transformation of HCBD under the anoxic conditions is still rare. This research project was aimed at improving our understanding of HCBD reductive dechlorination by unraveling the transformation pathway under the anoxic conditions. The main results of this study were as follows: the culture capable of anaerobic transformation of HCBD was enriched, and the anaerobic complete transformation pathway of HCBD was revealed. Microcosms inoculated with Xi river freshwater sediment samples were established with amendments of HCBD as electron acceptor and lactate as carbon source and electron donor. In the microcosms amended with HCBD, 62.5 μmol of HCBD was dechlorinated within 8 months. The daughter products of HCBD reductive dechlorination was identified and monitored by ISQ-LT gas chromatography-mass spectrometry (GC-MS), including (E)-1,1,2,3,4-PCBD (Pentachlorotrietadiene) , (3Z)-1,1,3,4-TeCBD (Techachlorotrietadiene), (E)-1,2,3-TCBD (Trichlorotrietadiene), (E,E)-1,4-DCBD (Dichlorotrietadiene) and 2-CBD (Chlorotrietadiene). In the microcosms amended with HCBD and trichloroethylene (TCE), 62.5 μmol of HCBD and 82 μmol TCE were transformed and dechlorinated also within 8 months; the daughter products of HCBD reductive dechlorination were the same as previously mentioned, and 78.5 μmol ethylene was the end product of TCE reductive dechlorination. Therefore, it is assumed that the pathway for HCBD reductive dechlorination via hydrogenolysis was proposed: HCBD→(E)-1,1,2,3,4-PCBD → (3Z)-1,1,3,4-TeCBD → (E)-1,2,3-TCBD → (E,E)-1,4-DCBD → 2-CBD. To sum up, through monitoring the reductive dechlorination process of hexachloro-1,3-butadiene in this research, the transformation products of the reductive dechlorination of hexachloro-1,3-butadiene were identified, a new anaerobic microbial transformation pathway of hexachloro-1,3-butadiene was analyzed, and our understanding of the reductive dechlorination of hexachloro-1,3-butadiene and its environmental fate was enhanced.